Hubungan Kepatuhan Minum Obat dengan Kualitas Hidup Pasien TB Paru di Puskesmas Mustika Jaya Tahun 2023 - Ade Ramadhani, Pingkan; Kiki Deniati (Jurnal Medicare, 2024)
Pulmonary tuberculosis is caused by a Mycobacterium tuberculosis infection, which attacks the lungs and causes respiratory issues such as chronic cough and shortness of breath. This study aims to analyze the relationship between medication adherence and the quality of life of pulmonary TB patients at Mustika Jaya Public Health Center in 2023. The research design is observational analytic with a cross-sectional approach, using a sample of 78 TB patients selected through purposive sampling. The instruments used include the Morisky Medication Adherence Scale (MMAS-8) for medication adherence and the WHOQOL-BREF questionnaire for quality of life assessment. Chi-square test results showed a significant relationship between medication adherence and quality of life, with a p-value of 0.00. A total of 51.7% of patients who adhered to their medication had a good quality of life. In conclusion, there is a significant positive relationship between medication adherence and quality of life in pulmonary TB patients at Mustika Jaya Health Center in 2023.